Do AAO-HNSF CORE Grants Predict Future NIH Funding Success?. (August 2014) - Eloy, Jean Anderson; Svider, Peter F.; Kanumuri, Vivek V.; Folbe, Adam J.; Setzen, Michael; Baredes, Soly
Objective: To determine (1) whether academic otolaryngologists who have received an American Academy of Otolaryngology— Head and Neck Surgery Foundation (AAO-HNSF) Centralized Otolaryngology Research Efforts (CORE) grant are more likely to procure future National Institutes of Health (NIH) funding; (2) whether CORE grants or NIH Career Development (K) awards have a stronger association with scholarly impact. Study Design and Setting: Historical cohort. Methods: Scholarly impact, as measured by the h-index, publication experience, and prior grant history, were determined for CORE-funded and non–CORE-funded academic otolaryngologists. All individuals were assessed for NIH funding history. Results: Of 192 academic otolaryngologists with a CORE funding history, 39.6% had active or prior NIH awards versus 15.1% of 1002 non–CORE-funded faculty ( P < .0001). Higher proportions of CORE-funded otolaryngologists have received K-series and R-series grants from the NIH ( P -values < .05). K-grant recipients had higher h-indices than CORE recipients (12.6 vs 7.1, P < .01). Upon controlling for rank and experience, this difference remained significant among junior faculty. Conclusions: A higher proportion of academic otolaryngologists with prior AAO-HNSF CORE funding have received NIH funding relative to their non–CORE-funded peers, suggesting that the CORE program may be successful in its stated goals of preparing individuals for the NIH peer review process, although further prospective study is needed to evaluate a "cause and effect" relationship. Individuals with current or prior NIH K-grants had greater research productivity than those with CORE funding history. Both cohorts had higher scholarly impact values than previously published figures among academic otolaryngologists, highlighting that both CORE grants and NIH K-grants awards are effective career development resources.